From omniscient narrator to involved participants: Places and spaces "activated" in the EHEC O104:H4 crisis 2011. (3rd November 2020) - Brinks, Verena; Ibert, Oliver
Abstract : Crisis management is often conceived from the position of an omniscient narrator, albeit the general consensus that crises are subjectively interpreted and experienced. The paper makes an analytical attempt to de‐homogenize the notion of crisis. We argue that the perception of crises differs and present a spatial perspective on crisis to foreground the positionality of different actor groups. By referring to the EHEC outbreak 2011 in Germany, we explore two spatial configurations that seem to be of particular relevance: territories embedded in a nested hierarchy and topologies of interconnected places. State authorities think and act strongly in terms of territorial borders and along sectoral boundaries. From their point of view, the crisis tends to be threatening due to its "transboundary" character. Medical experts, in contrast, coped with the crisis in trans‐local networks of colleagues. For this group, the crisis was also an opportunity to substantially enhance professional knowledge.